Luminescence properties and time-resolved spectroscopy of rare-earth doped SrMoO4 single crystals - Pankratova, Viktorija; Dunaeva, Elizaveta E.; Voronina, Irina S.; Kozlova, Anna P.; Shendrik, D.; Pankratov, Vladimir (Elsevier, 2022)
Luminescence properties of nominally pure and doped with Eu3+ and Pr3+ ions SrMoO4 single crystals grown by the Czochralski method have been studied. Thermal quenching of intrinsic emission of pure and doped SrMoO4 single crystals has been observed, as well as a correlation of thermal quenching activation energies with rare-earth ion concentration has been observed. Tunable laser was used to study time-resolved luminescence in a range from 10 K to room temperature. The effect of dopant nature and concentration on intrinsic emission and decay kinetics has been elucidated. --//-- Viktorija Pankratova, Elizaveta E. Dunaeva, Irina S. Voronina, Anna P. Kozlova, Roman Shendrik, Vladimir Pankratov, Luminescence properties and time-resolved spectroscopy of rare-earth doped SrMoO4 single crystals, Optical Materials: X, Volume 15, 2022, 100169, ISSN 2590-1478, https://doi.org/10.1016/j.omx.2022.100169. Article published under the CC BY-NC-ND licence.
The work of V. Pankratova was supported by the financial support of Scientific Research Project for Students and Young Researchers (SJZ/2020/05) realized at Institute of Solid State Physics, University of Latvia. The Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: SrMoO4; Eu3+; Pr3+; Photoluminescence; Time-resolved spectroscopy